Frankreichs Marktöffnung: Wirkung auf den Schienengüterverkehr. - Collon, Heidi; Dörr, Heinz (Deutscher Verkehrs-Verl., 2006)
Die Ausführungen sind im Kontext mit einer Studie zum Thema Schienengüterverkehr in der Fläche im Rahmen des Forschungsprogramms "Innovatives System Bahn" des österreichischen Bundesministeriums für Verkehr, Innovation und Technologie entstanden (Dörr, Frank et al. 2005). Diese Studie befasste sich neben regionalen Fallbeispielanalysen mit dem europäischen Umfeld bei der Allokation von bahngestützten Güterverkehren (www.freightonrail.at). difu

Market access to France's rail network began only recently although, organizationally, the rail tracks system and actual operations have existed separately since 1997 when the infrastructure provider RFF was founded. The rail network infrastructure is, especially for freight transport across various regions of France, badly in need of upgrading since, over the last 25 years, top priority has been given to the construction of TGV rail tracks. Freight carriage by rail is facing a difficult market situation vis-a-vis road transport, even over greater distances. The public has become aware of the need for a proper long-term transport policy, prompted by the inferno catastrophes in several Alpine tunnels. Freight transport by rail has so far been focused on those regions of France, which are keen on furthering their economic development. The dynamic EU-25 inland market fosters more transport links, and it is this opportunity that - in addition to France's state-owned railways - also more operators want to take advantage of. Future plans are available, and construction projects have been initiated along trans-European trunk routes across France. Still left to finalize are intermodal service patterns for links between regions and major trunk routes. difu
Keywords: Öffentlicher Verkehr; Güterverkehr; Schienengüterverkehr; Verkehrsnetz; Eisenbahn; Verkehrsinfrastruktur; Verkehrsachse; Eisenbahninfrastruktur; Eisenbahnpolitik; Marktöffnung; Liberalisierung; Transitverkehr